2014
DOI: 10.1111/ejh.12427
|View full text |Cite
|
Sign up to set email alerts
|

B‐cell receptor signalling and its crosstalk with other pathways in normal and malignant cells

Abstract: The physiology of B cells is intimately connected with the function of their B-cell receptor (BCR). B-cell lymphomas frequently (dys)regulate BCR signalling and thus take advantage of this pre-existing pathway for B-cell proliferation and survival. This has recently been underscored by clinical trials demonstrating that small molecules (fosfamatinib, ibrutinib, idelalisib) inhibiting BCR-associated kinases (SYK, BTK, PI3K) have an encouraging clinical effect. Here we describe the current knowledge of the speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
122
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 174 publications
(129 citation statements)
references
References 136 publications
3
122
0
4
Order By: Relevance
“…To our satisfaction, 9−11 not only retained PI3Kδ activity but also gained activity against BTK, Table 1. In our assay, SW13 (2) demonstrated subnanomolar inhibition of PI3Kδ, which was in agreement with the value reported by Shokat, and no inhibition of BTK. Replacing the methylene-linked quinazolinone group of SW13 with a 2-indanyl in 9 increased BTK activity to 67 nM while maintaining single-digit nanomolar activity against PI3Kδ.…”
supporting
confidence: 92%
“…To our satisfaction, 9−11 not only retained PI3Kδ activity but also gained activity against BTK, Table 1. In our assay, SW13 (2) demonstrated subnanomolar inhibition of PI3Kδ, which was in agreement with the value reported by Shokat, and no inhibition of BTK. Replacing the methylene-linked quinazolinone group of SW13 with a 2-indanyl in 9 increased BTK activity to 67 nM while maintaining single-digit nanomolar activity against PI3Kδ.…”
supporting
confidence: 92%
“…1,2 The small-molecule inhibitor of BTK kinase, ibrutinib, can disrupt CLL cells' capacity to interact with cells in the microenvironment by interfering with chemokine-receptor signaling, which is important for the chemotaxis of leukemia B cells to lymphoid tissues, and thus induce their massive and lasting mobilization in the peripheral blood. [1][2][3][4][5][6] The combined use of ibrutinib with anti-CD20 antibodies [7][8][9] or other monoclonal antibodies (mAbs) has been suggested for the treatment of patients with CLL because they use different mechanisms for antileukemia activity. Additionally, we and others have previously shown that microenvironmental interactions protect CLL and lymphoma cells from rituximab-induced cytotoxicity [10][11][12] and chemotherapyinduced apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…The most significant species (>10% in solution) were obtained for Ibrutinib. Once the solution pH increased, the following ionization sequence was obtained: LH 2 Figure 2, Ibrutinib is supposed to behave mostly as a neutral molecule LH 2 in biological relevant pH from 5 to 8. We also performed an ionic distribution analysis using Marvin and the obtained data were similar to the ones obtained with ACD/ percepta.…”
Section: Computational Prediction Of Pkmentioning
confidence: 99%
“…Ibrutinib (USAN, also known as PCI-32765 and marketed under the name Imbruvica) (Figure 1 Ibrutinib is currently under development by Pharmacyclics, Inc and Johnson & Johnson's Janssen Pharmaceutical division for additional B-cell malignancies including diffuse large B-cell lymphoma and multiple myeloma [1,2]. In January 2015, Ibrutinib was approved by the FDA for treatment of Waldenström's macroglobulinemia, a form of non-Hogkin´s lymphoma.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation